Comparative blood and urine metabolomics analysis of healthy elderly and young male Singaporeans - Chen, Liwei (2020)
Comparative metabolomics analysis of biofluids could provide information about the metabolic alterations in aging. To investigate the signature of multiple metabolic profiles associated with aging in an Asian population, we performed a pilot study in healthy Singaporeans, including 33 elderly and 33 young males. Fasting whole bloods were analyzed by routine hematology; the serum and urine metabolome profiles were obtained using NMR-based nontargeted metabolomics analysis and targeted lipoprotein analysis. Among the 90 identified compounds in serum and urine samples, 32 were significantly different between the two groups. The most obvious age-related metabolic signatures include decreased serum levels of albumin lysyl and essential amino acids and derivatives but increased levels of N-acetyl glycoproteins and several lipids and elevated urine levels of trimethylamine N-oxide, scyllo-inositol, citrate, and ascorbic acid but decreased levels of several amino acids, acetate, etc. Among 112 lipoprotein subfractions, 65 were elevated, and 2 were lower in the elderly group. These significantly age-varying metabolites, especially in the amino acid and fatty acid metabolism pathways, suggest that the regulation of these pathways contributes to the aging process in Chinese Singaporeans. Further multiomics studies including the gut microbiome and intervention studies in a larger cohort are needed to elucidate the possible mechanisms in the aging process.